Brak wystarczającego używania rozumu (kan. 1095 n. 1 KPK), poważny brak rozeznania oceniającego (kan. 1095 n. 2 KPK), przymus lub bojaźń (kan. 1103 KPK), symulacja zgody małżeńskiej (kan. 1101 §2 KPK) po stronie mężczyzny w sprawie (rozpoznanej z powództw - Góralski, Wojciech (Ius Matrimoniale, 2018)
On July, 28 2015 a (negative) sentence was passed in the Tribunal of the Roman Rota – in the second instance – in a case brought to judgment by an inheritor (a son) of the late Edward R. with respect to as many as four issues: insufficient use of reason (can. 1095, n. 1) by the complainant and/or a grave defect of discretion of judgment (can. 1095, n. 2) of the same person, force or grave fear (can. 1103), and/or simulation of marriage consent (can. 1101 §) by Edward. The special circumstances in the case included: conclusion of marriage by Edward when he was seriously ill, during his stay in a hospital, as well as a strong opposition of the complainant to his father’s marriage (the sentence of the Roman Rota was a preliminary in relation to the case brought to judgment in a state court concerning the succession of Edward’s estate). The rotal turnus c. Erlebach upheld the negative sentence of the first instance (in case of all issues), showing admirable insight.